The Canadian Permafrost Electrical Resistivity Survey (CPERS) database: 15 years of permafrost resistivity data - Teddi Herring; Antoni G. Lewkowicz; Alexandre Chiasson; Yifeng Wang; Robert G. Way; Joseph M. Young; Duane Froese; Sharon L. Smith; Brielle Andersen; Olivier Bellehumeur-Génier; Alexandre R. Bevington; Philip P. Bonnaventure; et al. (Arctic Science)
Permafrost landscapes are becoming increasingly susceptible to widespread thaw due to climate change. Collating historical and ongoing data are critical for assessing permafrost conditions and spatiotemporal changes. Electrical resistivity tomography (ERT) is a geophysical technique that has become standard practice for characterizing permafrost. However, resistivity data—particularly raw measurements—often go unpublished and unshared, resulting in missed opportunities for knowledge exchange and collaboration. To fill this gap, we created the Canadian Permafrost Electrical Resistivity Survey database and established clear guidelines for data archival and reuse. Here, we present the first release of the database, which currently houses 280 ERT datasets, including standardized metadata, collected between 2008 and 2022 in British Columbia, Labrador, Northwest Territories, Québec, Yukon, and Alaska. These data present unique opportunities to better understand spatial and temporal variability of permafrost conditions across North America.